PENGARUH MODEL MEANINGFUL INSTRUCTIONAL DESIGN (MID) TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA KELAS VIII SMP - Noviyana, Hesti (Lentera: Jurnal Ilmiah Kependidikan, 2019)
The problems studied in the study relate to the application of the Meaningful Instructional Design (MID) model and mathematical connection ability. The purpose of the study was to determine the effect of the Meaningful Instructional Design (MID) model on the mathematical connection ability of class VIII Even Semester 2 Middle School 2 Warkuk Ranau South Academic Year 2018/2019. The study used quasi-experimental methods. Analysis of research data to determine the effect of treatment given using the t test with data that is normally distributed and homogeneous. Based on the results of the data analysis, the average mathematical ability of the experimental class is higher than the average value of the control class, which is 76.56> 61.88. This is supported by the results of hypothesis testing obtained by the value t = 6.49. From the distribution table t at a significant level of 5% it is known that t = = 2.00 means t> t which is 6.49> 2.00, so it can be concluded that there is an influence of the Meaningful Instructional Design (MID) model on the mathematical connection ability of Grade VIII students Even the 2nd Middle School 2 Warkuk South Ranau Academic Year 2018/2019.